Advocacy and organizational engagement : redefining the way organizations engage - Bochenek, Lukasz M. (Emerald Publishing Limited, 2019)
In presenting a comprehensive overview on how to design and execute effective advocacy strategies for organizations, this book challenges the way organizational engagement used to be shaped. It proposes and provides tools for driving multilateral advocacy, where multiple actors and institutions cooperate together. For individuals, organizations and companies to be heard and have an impact, they need to cut through the noise by focusing on the quality and originality of their communications. This book analyzes the development of corporate communications and advocacy management within a number of contexts, including social media, marketing influencers, public relations and corporate social responsibility. To challenge the traditional perceptions of communications within companies and create a holistic approach to advocacy, Lukasz M. Bochenek blends theoretical reflection with practical implementation and provides the reader with management models, strategic advice, questionnaires and tools. This makes Advocacy and Organizational Engagement a beneficial read for both scholars and practitioners working in the field of organizational development and business strategy.
Introduction - why advocacy? why now? -- 1. What is advocacy and why it is important? -- 2. Strategic advocacy management - looking for a managerial model -- 3. From philanthropy to sustainability through CSR - what's next? societal context and changing role of the companies -- 4. Connecting with right audiences for a better impact - imperatives of the influencer marketing -- 5. Defining a conceptual model for advocacy strategy development -- 6. Shaping and (re-)defining the discourse content marketing in advocacy -- 7. Doing good and being good or simply getting it right - corporate crisis and defensive advocacy -- 8. New frontier for advocacy - towards an experience-based model of engagement -- Epilogue - what's next for advocacy.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Organizational learning -- Europe; Organizational change -- Europe; Business & Economics -- Organizational Development; Organizational theory & behaviour